Factors affecting anemia in end stage renal disease patients on presenting first time for dialysis to nephrologist - Muhammad Anees; Irfan Ilahi; Fazle Mateen; Sajjad Ahmad; Yasir Hussain; Muhammad Ibrahim (Pakistan Journal of Kidney Diseases, 2021)
Objective: To determineprevalence of anemia in ESRD patients presenting first time for dialysisand factors affecting it. Study Design: Observational descriptive study. Place and Duration of Study: Nephrology department of King Edward Medical University / Mayo Hospital, Lahore, from January 2014 to January 2016. Methodology: All patients presented in nephrology out patients department and with the indication for dialysis for the first time were included in study. Patients were asked when they consulted the Nephrologist for first time for the kidney disease and treatment modalities likeblood transfusion, Ironpreparation and EPO for the anemia. RESULTSOne hundred and seventy six (176) patients were enrolled in the study. Mean age of thepatients was 44.70 yearsand almost equal number of the patients were male 93 (52.8 %) and female 83 (47.2 %). Mean Hb was 8.47 gm/dL and majority of the patients 155 (88.1%) were anemic, hypoalbuminemic 164 (93.2%) and acidotic 157 (89.2 %). Seventy patients were getting medical treatment when they come to know about the kidney disease and only two patients were seen by Nephrologist at that time. Only 27(15.3%) patients were getting EPO for anemia while rest of the patients were getting either blood transfusion or no treatment for anemia. Mean dose of the EPO was 4000IU per week only in 69(39.2%) patients. CONCLUSION Majority of the patients were anemic on first presentationto nephrologist for dialysis. Anemia of the CKD patients was not properly managed due to unawareness and non-affordability of the expensive treatment of anemia.